Purinergic and Calcium Signaling in Macrophage Function and Plasticity - Desai, Bimal N.; Leitinger, Norbert (Frontiers in Immunology, 2014)
In addition to a fundamental role in cellular bioenergetics, the purine nucleotide adenosine triphosphate (ATP) plays a crucial role in the extracellular space as a signaling molecule. ATP and its metabolites serve as ligands for a family of receptors that are collectively referred to as purinergic receptors. These receptors were first described and characterized in the nervous system but it soon became evident that they are expressed ubiquitously. In the immune system, purinergic signals regulate the migration and activation of immune cells and they may also orchestrate the resolution of inflammation (1, 2). The intracellular signal transduction initiated by purinergic receptors is strongly coupled to Ca2+-signaling and coordination of these pathways plays a critical role in innate immunity. In this review, we provide an overview of purinergic and Ca2+-signaling in the context of macrophage phenotypic polarization and discuss the implications on macrophage function in physiological and pathological conditions.